EVALUASI RISIKO LONGSORLAHAN DAN MITIGASINYA DI KECAMATAN TAWANGMANGU TAHUN 2023 - Arlina Bunga Saputri; Setya Nugraha (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2024)
Tawangmangu District has an area of 7,003.04 Ha consisting of 10 villages/kelurahan. Tawangmangu District is located on the western slope of Mount Lawu with a slope that is predominantly rather steep to very steep with an altitude of ±1000 meters above sea level. The development of tourism activities, dryland agriculture, and the dense construction of house buildings have an impact on population pressure on land, so the risk of landslides increases. Landslide-prone areas are in the central part, namely Tawangmangu and Kalisoro Villages, Sepanjang Village in the west and central regions, Blumbang Village and Gondosuli Village in the middle and east, and Tengklik Village in the west. The purpose of this study is to determine the level of landslide risk and mitigation recommendations both structurally and non-structurally. Descriptive qualitative research methods include determining vulnerability, vulnerability, community capacity, and landslide risk using observational data scoring. The results showed that villages/kelurahan in Tawangamngu District that have a very high risk of landslides are Nglebak Village, Sepanjang Village, Bandardawung Village, and Tawangmangu Village.